Geophysical Investigation as an Aid to Understanding Complex Geological Terrain: A Case of Yikpata Transition Zone in Share, North-Central Nigeria - DANGA, Onimisi Abdulmalik; OBASAJU, Daniel Opemipo; GOMINA, Ochu David; IJALEYE, Olumayowa Temitope; ADOZE, Usman Jose (GeoScience Engineering, 2021)
A geophysical method of investigation has been deployed in order to give a quick overview of the nature and the rapidly changing subsurface lithologies that characterized Yikpata, Share, Kwara State, Nigeria. A total of nine (9) vertical electrical soundings (VES), using Schlumberger Array uniformly divided into three groups: basement, basement/sedimentary boundary and sedimentary terrain, and horizontal profiling (HP) using Wenner Array were deployed for this study. The study revealed variation in the subsurface resistivity, thus depicting changes in lithology/rock types along this basement-sedimentary contact zone. The interpretation revealed that the Basement Complex terrain consists of 3-4 geoelectric layers: the topsoil, the weathered, weathered/fractured basement and the fractured basement. Depths beyond ≥ 12 m where the fractured basement occurs can be target for groundwater exploration and structurally controlled mineralization. The resistivity values around the Basement/Sedimentary unconformity zone shows about 3 – 4 geoelectric layers. The resistivity values show remarkable characteristics of the basement and the sedimentary terrains and also reflect the rapidly changing subsurface geology in the area. In the sedimentary terrain, 4 geoelectric layers were delineated: Top soil, clayey sand, sandy clay and clay. Geoelectric sections reveal the variation in the subsurface lithology laterally and vertically. The study has shown that the resistivity method can be an aid to understand complex geologic environments with rapidly changing subsurface geology. Also, the knowledge of the geology of an area is very important in order to make sensible geophysical interpretation. Keywords: Basement complex; Electrical resistivity, Geoelectric; Vertical electrical sounding.